Sistema de ciber seguridad para la red de comunicación de la Universidad Técnica de Babahoyo basado en sistemas de código abierto. - Muñoz Vera, Carmen Adriana (2023)
This case study aims to modernize the IT Network Infrastructure through the implementation of hyperconvergence that allows sessions by modules, where the launch of a firewall module dedicated to controlling network traffic is prioritized, as well as proposing security politics. Based on the firewall configurations discovered during the research process, the development of this case study is proposed in order to make network scalability more flexible, reinforce security support for its users, with this it is intended to present security policies that increase the security protocols in force. Detailed and specific objectives to be met: Analyze and identify the weak points of the computer network, Present the respective corrections that require a minimum effort to maintain the low cost of execution, Propose the respective adaptations and security protocols that maintain considerable benefits and low costs implementation for the computer network. Additionally, it is highlighted that thanks to this case study, the software requirements that the Technical University of Babahoyo needs to implement a set of rules and configurations that increase protection against computer attacks, generating greater prevention, were made known. which means greater confidence for network users.